Practices and attitudes in the use of digital tools in the writing process among Peruvian university students of business administration - Arias-Chávez, Dennis (2025)
This study describes the practices and attitudes of 350 business administration students from three universities from Lima (Peru), regarding the use of digital tools in the writing process. Using a quantitative, descriptive and cross-sectional approach, a single questionnaire is administered that addressed the use of digital tools, academic performance, and plagiarism detection, which are analyzed using the statistical software Jamovi. The results show that 63.7% of the students use tools for paraphrasing and 33.7% for drafting complete essays. Detection by instructors is low (35.1% for paraphrasing and 22% for essays), highlighting a significant gap in technological knowledge. Additionally, 74.6%of students are aware of a peer using these tools for paraphrasing and 56.3% for complete essays. In conclusion, attitudes toward the use of digital tools are ambivalent, with many students neither agreeing nor disagreeing, reflecting uncertainty about their academic and ethical impact.